Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1108/02621719910265577
|View full text |Cite
|
Sign up to set email alerts
|

Mind mapping in executive education: applications and outcomes

Abstract: Developed by Tony Buzan in 1970, mind mapping is a revolutionary system for capturing ideas and insights horizontally on a sheet of paper. This paper illustrates the technique of mind mapping, and highlights its specific applications in a variety of contexts based on our work in executive education and in management development consulting. Positive outcomes of the approach are described as well as reactions of executive students to mind mapping. We conclude with a rationale of why we believe mind mapping works… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 11 publications
1
77
0
7
Order By: Relevance
“…When drawing Mind Maps, there are a few essential techniques (Gelb, 1998;Mento, Martinelli & Jones, 1999;Reed, 2005): allowing other ideas to be organized (Buzan, 2002). For instance, if "electronic map" or "audio guide" (at the attributes level) are written on the trunk right after the start of the "electronic tour guide design" brainstorming session, the subsequent items on the branches will be limited, thus ceasing the flow of the thought process.…”
Section: Developing the Prototypementioning
confidence: 99%
“…When drawing Mind Maps, there are a few essential techniques (Gelb, 1998;Mento, Martinelli & Jones, 1999;Reed, 2005): allowing other ideas to be organized (Buzan, 2002). For instance, if "electronic map" or "audio guide" (at the attributes level) are written on the trunk right after the start of the "electronic tour guide design" brainstorming session, the subsequent items on the branches will be limited, thus ceasing the flow of the thought process.…”
Section: Developing the Prototypementioning
confidence: 99%
“…Besides, as indicated by Jones, Pierce, & Hunter [3], a good mind mapping enables learners to perceive relationships of the main concepts of a specific issue and gain understanding and concept of the subject more quickly and better than trying to understand from verbal explanation alone. Besides, results from several researches show that use of mind maps can significantly enhance learning, memory, motivation and creativity of students [4]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, numerous studies have confirmed the positive outcomes of using mind map in learning (Farrand et al, 2002;Mento et al, 1999). In learning History, a student could build a mind map by interconnecting relationships that emerge among the historical events.…”
Section: Comprehensive Approachmentioning
confidence: 96%